European Union: From social integration to social state - Brkić Luka (Međunarodni Problemi, 2004)
This paper analyzes recent free trade arrangements from a positive political economy perspective. In contrast to most other literature, which fails to take into account geographical factors, it is argued here that proximity and transportation costs play an important role in trade arrangements. Another important also largely neglected factor is the degree of social cohesion in terms of labor standards among potential trading partners. Accepting social integration might also be a condition for admitting those countries to the agreement. Changes of trade policy over time can therefore be explained by changes in the relative political influence of the sectors considered. The other important factors are, of course, a change in the degree of retaliation, leading to lower tariffs under higher retaliation, and a leveling of social standards. Redistribution across countries could also considerably change the optimal rate of tariff. The EU with its regional cohesion funds might be a good example of how those are used as a side-payment for diminishing the social divergence in the member countries. Countries with higher standards should only be willing to integrate when others raise their social standards as well. The negotiations about the social protocol in the EU indicate that this is in fact the case. More than 40 years of European integration have led to an habituation of thinking of the European Community as something ideologically neutral, which transcends normal political debate. European issues, it seems, do not fit the structure of the usual right-left ideological controversy. The only open fault-line in European politics is between advocates of "more" and those of "less" integration. The paper explores the potential cognitive and political gains of a change of perspective. It argues that the issue of more or less integration is often not interesting in itself but only to the degree that it influences the content of policies. It further shows that the policies at stake are normally such, that they can be usefully debated in the right-left framework. The decision about the site of policy control - national or European - is often only the guise in which a decision about the redrawing of the boundary between market and state, between the sphere of competitive allocation and the sphere of political coordination, materializes. This paper aimed at stressing the fundamental differences between conventional and contractarian constitutional orders. To achieve it, we have used the concept of common knowledge and have related it to its political philosophy background, especially with regard to communication and induction. The former generates a spontaneous social order - it is an evolutionist view that belongs to the Hume - Menger - Hayek tradition. The latter produces a contractarian vision shared by the Brennan-Buchanan-Tullock tradition. We consider here a basic distinction between institutions and conventions. An institution is considered as a formal, explicit rule, while a convention appears to be a tacit, implicit agreement. The former can be associated with contractarian constitutionalism, whereas the latter is related to evolutionism. In this context, institutions should not be understood as formalized conventions (such as law in Hayek). They are rather the expression of a voluntary and deliberate agreement, of a covenant. The application describes features relevant to the development of a European constitution and the corresponding unified legal system. It requires a clear vision of what a European "state" is meant to be or become. Then, once a constitutional setting is chosen, one must address the question of legal organization, in particular the nature of administrative law. Two different acceptation of law are thus associated with the two concepts of convention and contractarian institution. The former can be regarded as customary rule a kind of common knowledge that emerges from tradition and sympathy. By contrast, the latter is the place of explicitly created common knowledge. If it is to become more integrated, Europe will have to tackle this constitutional question, either in an evolutionary or in a contractarian way.